2008
DOI: 10.1243/13506501jet392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of counterface topography on sliding friction and wear of some elastomers under dry sliding conditions

Abstract: In this work, the friction and wear behaviour of acrylonitrile butadiene rubber (NBR), hydrogenated acrylonitrile butadiene rubber (HNBR), acrylate rubber (ACM), and fluoroelastomer (FKM) against steel surfaces under unidirectional dry sliding conditions have been studied. The influence of surface roughness of the steel counterface on friction and wear was studied using a block-on-ring test configuration. At low load, the friction coefficient decreased after a runningin period and the wear was insignificant, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The test procedure has been described in detail elsewhere. 27 Before each test, the sample surfaces were cleaned with heptane to remove possible contaminations due to the exposure to air. Care was taken to avoid any damage of sample surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…The test procedure has been described in detail elsewhere. 27 Before each test, the sample surfaces were cleaned with heptane to remove possible contaminations due to the exposure to air. Care was taken to avoid any damage of sample surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…Adhesion and deformation are the two most important mechanisms that are responsible for the frictional behaviors of elastomers [55,56]. The high friction of uncoated HNBR and NBR under dry conditions show that not only deformation, which can be related to the relatively low hardness, but also adhesion, which can be seen as a dissipative stick-slip process on molecular level, are influential factors for the dry frictional behaviors [57][58][59][60]. This is in good agreement with Rabinowicz's studies, which indicated that low ratios of surface energy/hardness are associated with better surface interactions and also less adhesion [61,62].…”
Section: Coefficient Of Frictionmentioning
confidence: 99%
“…It is widely accepted that adhesion, which is the result of samples exhibiting stick‐slip behavior, plays a major role in the friction of materials exhibiting high modulus of elasticity. Additionally, hysteresis friction is the resulting behavior of samples when their internal friction is the more dominant component in the friction of materials with low moduli of elasticity . The wear behavior of rubber is a complex phenomenon and involves more than one mechanism.…”
Section: Introductionmentioning
confidence: 99%